Geotourism activity evaluation: case study in Langkawi Geopark, Malaysia - Hassan, Hamimah; Komoo, Ibrahim; Leman, Mohd. Shafea (Asian Academic Research Associates, 2017)
Langkawi Island has long been known as a tourist destination since the 1980s. Since being recognised as a geopark in 2007, the development of the island has been far more challenging. The objective of this paper is to analyse tourist activities in Langkawi Geopark using geotourism scales, known as SKALAGEO, which was developed for the current study. An in-depth literature review propose that geotourism behaviour comprises of 4 dimensions; that are appreciation (4 items), learning (5 items), culture (3 items) and geological heritage (5 items). Questionnaires were developed and distributed in Langkawi Geopark using convenience sampling. The efforts yielded 339 respondents who agreed to take part in the survey and SPSS analysis was used for the data gathered. The reliability analysis results shows that the 18 scales of SKALAGEO has high reliability scores of 0.927. The descriptive analysis revealed that appreciation has the highest average score (4.5), comparing to other dimensions; learning, culture and geological heritage. The results indicated that the respondents in this study match to the characteristics of geotourist. Regression analysis was also conducted and positive relationship were found between geotourism behavior and tourist satisfaction. The research findings provide supports to the government efforts in improving activities related to geotourism as well as promoting the island as a UNESCO global geopark. In order to improve the quality of geotourism attraction, it is proposed that improvement in knowledge delivery related to geological process need to be increased as this will boost higher tourist satisfaction level among the tourists. Geotourism behavior scales used in this study are found as a useful tool in measuring geotourism behaviour and, therefore, the study has contributed to enhancing knowledge in geotourism literature.